A Modern Approach to The Treatment of Rectal Prolapse in Children - Yusupov Shukhrat Abdurasulovich; Atakulov Jamshed Ostonakulovich; Davranov Bobir Latibovich; Raximov Anvar Komilovich (Zien Journals, 2023)
During the period from 2010 to 2022, we followed up 212 children with rectal prolapse (RPL), 135 of them were boys, 77 - girls; 11 children under 1 year of age, 134 - from 1 to 3 years, 59 - from 4 to 7 years, and 8 children older than 7 years. Stage I CAP was revealed in 69, II -y 112, III - in 31 patients. Intestinal and stomach diseases in 121 children (dysentery, dyspepsia, enterocolitis in 67, chronic constipation in 54), respiratory diseases in 22, urinary and genital diseases in 22, continuous potty sitting in 21, rectal polyps in 10, severe post disease hypotrophy in 11, gluteal trauma in 5.
Keywords: rectal prolapse; review; children